CO2-assisted fabrication of silica gel adsorbent in honeycomb rotary wheels for air dehumidification - You, Junjie; Qin, Junbo; Du, Chuanqing; Fu, Jianhua; Cheng, Siqing (Frontiers in Chemistry, 2022)
A honeycomb rotary wheel fabricated from sheet adsorbent of silica gel is a competitive drying facility for air dehumidification in modern drying and air conditioning industries due to its large contacting area (3000 m2/m3) and the rapid diffusion of the adsorbate compared to silica gel pellets. The delicate preparation procedure of hygroscopic silica gel is paramount for improved adsorption capacity by optimizing the surface area, pore size and pore volume of silica gel. In this paper, silica gel adsorbent in honeycomb rotary wheel was fabricated by neutralizing the impregnated water glass solution with a modulus of 3.3 on the glass fiber sheet of the honeycomb matrix using CO2 at different pressure at room temperature instead of corrosive acids. The as-obtained silica gel absorbent was characterized by XRD, scanning electronic microscopy (SEM), specific surface area & pore size analyzer and dynamic vapor/gas sorption analyzer. The results showed that the as-obtained silica gel adsorbent is uniform in size and tunable in terms of specific surface area, pore size, pore volume, adsorption capacity by CO2 pressure. The typical silica gel fabricated by CO2 of 0.25 MPa with a specific surface area of 764.86 m2/g, an average micropore size in diameter of 2.94 nm and a pore volume of 0.45 ml/g delivers a saturated adsorption capacity of as high as 287.24 mg/g at RH 50%, which is the best in adsorption performance compared to the previous reported results. This provides a new strategy for environmentally friendly manufacturing of silica gel adsorbent in honeycomb rotary wheel for air dehumidification.